1989
DOI: 10.1021/bi00444a042
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification of a critical sulfhydryl group in the acetylcholine receptor: cysteine-222 of the .alpha.-subunit

Abstract: Chemical modification of the Torpedo californica acetylcholine receptor (AcChR) by the fluorescent agent N-(1-pyrenyl)maleimide (PM) under nonreducing conditions resulted in the labeling of cysteine residues in all subunits and marked inhibition of the AcChR ion channel opening [Clarke, J. H., & Martinez-Carrion, M. (1986) J. Biol. Chem. 261, 10063-10072]. The PM alkylation kinetics are not affected by the presence of agonists or a competitive antagonist. The PM-labeled alpha-subunit has been purified and dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The covalent modification could have little effect on function, or it could have canceling effects, for example, by decreasing conductance and increasing channel open time. Nevertheless, our finding that aCys222 and aLeu223 are unaffected by the highly hydrophilic MTSEA is consistent with the labeling of these residues by highly hydrophobic labels (Marquez et al, 1989;Blanton & Cohen, 1994). The screening approach we have used identifies many residues at the water-accessible surface but not necessarily all such residues.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The covalent modification could have little effect on function, or it could have canceling effects, for example, by decreasing conductance and increasing channel open time. Nevertheless, our finding that aCys222 and aLeu223 are unaffected by the highly hydrophilic MTSEA is consistent with the labeling of these residues by highly hydrophobic labels (Marquez et al, 1989;Blanton & Cohen, 1994). The screening approach we have used identifies many residues at the water-accessible surface but not necessarily all such residues.…”
Section: Discussionsupporting
confidence: 79%
“…The only prior indication of this was the specific photolabeling of the extracellular end of aMl in Torpedo ACh receptor by the noncompetitive inhibitor quinacrinc azide (DiPaola et al, 1990; Karlin, 1991). Other evidence indicated that some residues in the middle of Ml are accessible to highly hydrophobic reagents, possibly reaching Ml from the lipid bilayer (Marquez et al, 1989;Blanton & Cohen, 1994). From the effects of the mutation of one of these residues, the cysteine in yM 1 aligned with aCys222, Lo et al (1991) concluded that it is not exposed in the channel.…”
Section: Discussionmentioning
confidence: 99%
“…The M4 subunit is separated by a long cytoplasmic loop and probably lies outside the second ring of helices (see references 12 and 13 for good reviews). Photolabeling experiments with pyrene maleimide and 3-trifluoromethyl-3-(m-[ 12511 ]iodophenyl)diazirine have identified the faces of the Ml and M4 helices that face the bilayer ( 14,15).…”
Section: Origins Of Selectivity For Negatively Charged Phospholipidsmentioning
confidence: 99%
“…To understand the interrelationship between structure and function is an important challenge in characterizing the mechanism of action of the AChR. Selective chemical modifications of cysteine residues in the AChR have been used over the past 20 years as a powerful approach to probe structure-function relationships (Huganir and Racker, 1982; Kao et al, 1984;Clarke and Martinez-Carrion, 1986;Kao and Karlin, 1986; Yee et al, 1986;Mosckovitz and Gershoni, 1988;Marquez et al, 1989). Early attention focused on the pair of cysteines at the ACh binding site (Kao et al, 1984; Kao and Karlin, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of the yCys4l6 and/or yCys420 to Phe or Ser did not show significant functional effects (Pradier et al 1989), whereas mutations of the ,yCys451 to Phe or Ser showed substantial inhibition of the channel activity (Li et al, 1990) as measured electrophysiologically by whole-cell current responses to ACh. A cysteine in the Ml transmembrane segment of the a subunit (aCys222) can be selectively labeled by PM (Marquez et al 1989), and mutation of this Cys to Ser (Mishina et al, 1985) in Torpedo AChR or mutation of an equivalent cysteine in the a subunit of murine AChR to Ser (Lo et al, 1991) resulted in no functional changes of the receptors. FIGURE 1 Position of the aCys418 in the globular AChR.…”
Section: Introductionmentioning
confidence: 99%